Removal of Cu and Zn Ions from Aqueous Solution Using Sodium Alginate and Attapulgite Composite Hydrogels - Dajian Huang; Wenbo Wang; Aiqin Wang (Adsorption Science & Technology)
A series of sodium alginate-g-sodium acrylate/attapulgite (NaAlg-g-PNaA/APT) composite hydrogels were used as adsorbents to adsorb Cu 2+ and Zn 2+ from aqueous solutions. The effect of common variables including the content of APT, pH value, contact time and initial concentration of metal ions on the adsorption properties of the composite hydrogels for the adsorption of Cu 2+ and Zn 2+ ions was investigated using a batch adsorption technique. The results show that the composites evaluated have an excellent adsorption capacity and fast adsorption rate for both Cu 2+ and Zn 2+ ions. Repeated adsorption–desorption experimental results show that the composite hydrogels have a good reusability and stability, and 50% of the original adsorption capacity can be retained after being reused five times. The pseudo-second-order equation and the Langmuir equation best describe the adsorption kinetics and isotherms, respectively.